2000
DOI: 10.1155/2000/218531
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in Elderly Patients: Impact of Laparoscopic Cholecystectomy

Abstract: The use of laparoscopic cholecystectomy (LC) in elderly patients may pose problems because of their poor general condition, especially of cardiopulmonary function. Moreover, these patients present with acute cholecystitis and associated common bile duct stones more often than their younger counterparts. From 1990 to 1999, the authors performed 943 LCs; 31 (3.2%) were attempted on elderly patients, 11 (35%) of which were on an emergency basis because of acute cholecystitis, cholangitis or acute biliary pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…3 It speaks to the limited physiologic reserve of this patient group but remains below the rate reported for open cholecystectomy. 7 While Uecker et al 5 and Magnuson et al 8 did not see a benefit of LC with respect to morbidity and mortality in the management of acute biliary tract disease in the octogenarian, our data suggest otherwise. Uecker et al reported a complication rate of 56% after laparoscopic intervention and 14% after open cholecystectomy for acute cholecystitis.…”
Section: Resultscontrasting
confidence: 56%
“…3 It speaks to the limited physiologic reserve of this patient group but remains below the rate reported for open cholecystectomy. 7 While Uecker et al 5 and Magnuson et al 8 did not see a benefit of LC with respect to morbidity and mortality in the management of acute biliary tract disease in the octogenarian, our data suggest otherwise. Uecker et al reported a complication rate of 56% after laparoscopic intervention and 14% after open cholecystectomy for acute cholecystitis.…”
Section: Resultscontrasting
confidence: 56%
“…Several authors [35,39] have reported that LC with intraoperative hemodynamic monitoring can be safely performed in elderly patients; however, it is important to use the gasless technique [26] or a gradual abdominal insufflation with a pressure always <12 mmHg and a limited 10°head-up tilt [9].…”
Section: Resultsmentioning
confidence: 99%
“…In the era of laparoscopic cholecystectomy, few studies have reported the results of this procedure in the elderly [4,15], and no study has specifically addressed single-stage laparoscopic management of gallstones and CBD stones in patients of advanced age. The current prospective study aimed to evaluate the results of singlestage laparoscopic cholecystectomy and CBD exploration in a series of unselected patients older than 70 years, and to compare them with the results in a control group of younger patients treated with the same type of approach by the same surgical team during the same period.…”
mentioning
confidence: 99%